Low-density lipoprotein receptor mutational analysis in diagnosis of familial hypercholesterolemia - Bourbon, M. (2017)
PURPOSE OF REVIEW: To present up to date evidence on the pathogenicity of low-density lipoprotein receptor (LDLR) variants and to propose a strategy that is suitable for implementation in the clinical work-up of familial hypercholesterolaemia. RECENT FINDINGS: More than 1800 variants have been described in the LDLR gene of patients with a clinical diagnosis of familial hypercholesterolaemia; however, less than 15% have functional evidence of pathogenicity. SUMMARY: The spectrum of variants in the LDLR identified in patients with clinical familial hypercholesterolaemia is increasing as novel variants are still being reported. However, over 50% of all LDLR variants need further evidence before they can be confirmed as mutations causing disease. Even with applying the recent American College of Medical Genetics variant classification, a large number of variants are still considered variants of unknown significance. Before obtaining an undisputable confirmation of the effect on the expression and activity of the LDLR, reporting these variants as part of a clinical diagnosis to the patient holds the risk that it might need to be withdrawn in a later stage. An investment should be made to develop functional assays to characterize LDLR variants of unknown significance for a better patient diagnosis and to prevent confusion in the physician's office.